Perbandingan Pendekatan Pembelajaran Saintifik dan Ekspositori terhadap Hasil Belajar Matematika Siswa SMP Swasta di Kecamatan Pancoran Jakarta Selatan - Zulrahmat Togala (Universitas Indraprasta PGRI, 2015)
This aims of study to determine the influence of scientific learning approaches to mathematics achievement. The method used in this study is the experimental method, sampling technique using random sampling techniques. The instrument for data collection on research in the form of a multiple choice test consisting of 25 items. Data analysis technique used is the average difference (test), and based on the calculation of the test, showed = 2.282 and table = 1.68 at significance level of 5% or ? = 0.05, which means test > tabel (2.282> 1.68), then H0 rejected and H1 accepted. It can be concluded that there are significant scientific approach to students’ mathematics achievement.